The relationship between self-control and internet gaming disorder and problematic social networking site use: the mediation effects of internet use motives - Zhou, Ruoyu; Morita, Nobuaki; Zhu, Chunmu; Ogai, Yasukazu; Saito, Tamaki; Yang, Wenjie; Ogawa, Mitsue; Zhang, Hong (Frontiers in Psychiatry, 2024)
Introduction This study aimed to explore the relationships between problematic social networking site use (PSNSU), Internet Gaming Disorder (IGD), internet use motives, and self-control among university students in China and Japan. Specifically, it investigated the indirect effects of self-control on IGD and PSNSU through various internet use motives, considering gender differences. Methods A sample of 697 university students (465 females; 397 Chinese) was surveyed. Path analysis was conducted separately for male and female users to examine the relationships between self-control, internet use motives, IGD, and PSNSU. Results The results indicated that self-control had significant indirect effects on IGD through enhancement (β = 0.096**, p = 0.005), social (β = -0.090**, p = 0.007), and conformity (β = -0.117**, p = 0.001) motives, but these effects were observed only in the male group. Self-control also exhibited indirect effects on PSNSU through enhancement, social, coping, and conformity motives, with a greater impact observed on PSNSU than on IGD. Gender differences in mediating effects were identified, with males and females showing distinct patterns. Discussion The findings highlight the importance of understanding gender differences and motivational factors in problematic internet use. These insights contribute to a better understanding of how internet use motives influence IGD and PSNSU in different contexts.